Evaluation of Different Power of Near Addition in Two Different Multifocal Intraocular Lenses - Ugur Unsal; Gonen Baser (Journal of Ophthalmology)
Purpose. To compare near, intermediate, and distance vision and quality of vision, when refractive rotational multifocal intraocular lenses with 3.0 diopters or diffractive multifocal intraocular lenses with 2.5 diopters near addition are implanted. Methods. 41 eyes of 41 patients in whom rotational +3.0 diopters near addition IOLs were implanted and 30 eyes of 30 patients in whom diffractive +2.5 diopters near addition IOLs were implanted after cataract surgery were reviewed. Uncorrected and corrected distance visual acuity, intermediate visual acuity, near visual acuity, and patient satisfaction were evaluated 6 months later. Results. The corrected and uncorrected distance visual acuity were the same between both groups (p=0.50 and p=0.509, resp.). The uncorrected intermediate and corrected intermediate and near vision acuities were better in the +2.5 near vision added intraocular lens implanted group (p=0.049, p=0.005, and p=0.001, resp.) and the uncorrected near vision acuity was better in the +3.0 near vision added intraocular lens implanted group (p=0.001). The patient satisfactions of both groups were similar. Conclusion. The +2.5 diopters near addition could be a better choice in younger patients with more distance and intermediate visual requirements (driving, outdoor activities), whereas the + 3.0 diopters should be considered for patients with more near vision correction (reading).